Extraction and characterization of novel multifunctional peptides from Trachinus Draco (greater weever) myofibrillar proteins with ACE/DPP4 inhibitory, antioxidant, and metal chelating activities. Issue 5 (9th March 2020) - Kula, Elif; Kocadag Kocazorbaz, Ebru; Moulahoum, Hichem; Alpat, Senol; Zihnioglu, Figen
Abstract: Marine organisms represent a great source of natural bioactive molecules, from which bioactive peptides are of great importance in biomedicine application in many diseases such as diabetes and its related complications. In this study, greater weever ( Trachinus Draco ) myofibrillar proteins were sequentially hydrolyzed and the different RP‐HPLC purified fractions were tested for potential inhibitory activities of ACE and DPP4, in addition to metal chelation and antioxidant activities. Four fractions were found to have high levels of activity (with two peptides being multifunctional) and were subsequently sequenced using the de novo sequencing method. The results indicate that the peptides are novel and highly effective for each related activity compared to reference molecules. The current findings suggest these multifunctional peptides as promising therapeutics against oxidative stress, hypertension, and diabetes. Practical applications: We have described the finding of two multifunctional bioactive peptides from Trachinus Draco (greater weever) myofibrillar proteins having two or more activities. They have ACE inhibitory, DPP4 inhibitory, antioxidant, and metal chelation activities. These new peptides could be used for future biomedicine applications as a stand‐alone treatment, in combination with other molecules, or as a supplement. Furthermore, after identification of their sequence in our work, it would have a great potential to be artificially synthesized. The field of food supplements could be explored further. Abstract : Bioactive peptides are of utmost importance for new drug discovery while marine organisms, particularly fish, represent a great reservoir for novel biomolecules identification. The current work was able to describe 2 multifunctional bioactive peptides from Trachinus Draco (Greeter weveer) myofibrillar proteins after sequential hydrolysis and HPLC fractionation. The de novo sequenced peptides showed ACE inhibitory, DPP4 inhibitory, antioxidant, and metal chelation activities that have a great potential for aging‐related pathologies such as diabetes and hypertension.